2003
DOI: 10.1021/bi027019u
|View full text |Cite
|
Sign up to set email alerts
|

A Major Role for a Set of Non-Active Site Mutations in the Development of HIV-1 Protease Drug Resistance

Abstract: A major problem in the chemotherapy of HIV-1 infection is the appearance of drug resistance. In the case of HIV-1 protease inhibitors, resistance originates from mutations in the protease molecule that lower the affinity of inhibitors while still maintaining a viable enzymatic profile. Drug resistance mutations can be classified as active site or non-active site mutations depending on their location within the protease molecule. Active site mutations directly affect drug/target interactions, and their action c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(149 citation statements)
references
References 33 publications
11
135
1
2
Order By: Relevance
“…Dissociation Constants. The K i values for the wild-type enzyme with all of the inhibitors tested were subnanomolar to low nanomolar in agreement with other studies (Table 4) (5,(27)(28)(29). The V6 variant showed a large decrease in susceptibility to ritonavir.…”
Section: Resultssupporting
confidence: 91%
“…Dissociation Constants. The K i values for the wild-type enzyme with all of the inhibitors tested were subnanomolar to low nanomolar in agreement with other studies (Table 4) (5,(27)(28)(29). The V6 variant showed a large decrease in susceptibility to ritonavir.…”
Section: Resultssupporting
confidence: 91%
“…It was originally believed that non-active site mutations were acquired to regain the loss of catalytic activity due to active site mutations. Recent studies from our laboratory and others have shown that many non-active site mutations in HIV-1 subtype-B proteases will contribute to decreasing the binding affinity of inhibitors, while maintaining catalytic efficiency (10,(22)(23)(24)26,27). In this study we provide insights into the effects of natural polymorphisms and the contributions to resistance made by therapy-selected active site and non-active site mutations found in the CRF_01 AE protease.…”
Section: Discussionmentioning
confidence: 79%
“…The Ile84 residue is located in the center of the active site and we previously suggested that the I84V mutation may function to destabilize the interactions of the core of the inhibitor and its interactions with the flaps (23). Previous studies have also shown the importance of mutations in the flaps in providing a high level of resistance (10,22,23,26), and that the addition of non-active site mutations may decrease binding affinity by destabilizing the flaps in the bound conformation decreasing binding affinity (23). Recent studies by Yanchunas and colleagues, utilizing thermodynamic and modeling techniques, have suggested the importance of ATV P2 and P2â€Č groups interactions with Ile50 in maintaining binding affinity (33).…”
Section: Structural Analysis Of Atv Bindingmentioning
confidence: 99%
“…Chang and Torbett (2011) demonstrate that stability is compromised by the acquisition of primary mutations and this loss of stability can be rescued by known compensatory mutations, sometimes in excess of the reference stability. Muzammil et al (2003) and Louis et al (2011) have shown that patterns of up to ten or more resistance mutations do not necessarily suffer from reduced stability relative to the wildtype, and that nonactive site mutations can lead to resistance in certain sequence contexts. In figure 3A, the change in statistical Potts energies, DE ÂŒ E À E ref is plotted versus the change in thermal stability, where E and E ref are the statistical energies of the mutated and reference sequences corresponding to each pair of stability measurements.…”
Section: Protease Mutations Protein Stability and Replicative Capacitymentioning
confidence: 99%